ANALYSIS OF DOPPLER ULTRASOUND INDICATORS IN YOUNG PATIENTS WITH METABOLIC SYNDROME - Abdusodikovich , Shahboz; Gaybiyev, Akmal (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The Cardiovascular Risk in Young Finns study demonstrated that various metabolic syndrome criteria in adults aged 32 ± 5 years are associated with a significant increase in carotid intima-media thickness (cIMT) and decreased vascular compliance (CAC), indicating the onset of atherosclerotic disease well before clinical manifestations (1). Similarly, recent data have demonstrated that the presence of risk components of metabolic syndrome in young and middle-aged adults is significantly associated with increased cIMT and other markers of subclinical atherosclerosis.